A case of eosinophilic granulomatosis with polyangiitis as a mimicker of IgG4-related disease. (2nd July 2020) - Kanda, Ryuichiro; Kubo, Satoshi; Nakano, Kazuhisa; Kawabe, Akio; Nawata, Aya; Hanami, Kentaro; Nakayamada, Shingo; Tanaka, Yoshiya
Abstract: A 62-year-old woman was admitted to our hospital because of fever, renal dysfunction, eosinophilia, and the presence of MPO-ANCA. Based on the renal pathological examination which showed granuloma lesion with eosinophils and crescentic glomerulonephritis, eosinophilic granulomatosis with polyangiitis (EGPA) was diagnosed. On the other hand, laboratory examination showed elevated serum IgG4 levels and renal pathological examination showed marked lymphoplasmacytic infiltration and fibrosis surrounding nest "Bird's eye pattern, " which were characteristic of IgG4-related kidney disease (IgG4-RKD). Because there are cases when EGPA has clinical features of IgG4-RKD, we should be careful about diagnoses of IgG4-RKD in patients with EGPA.